Alternate quinone coupling in a new class of succinate dehydrogenase may potentiate mycobacterial respiratory control. Issue 5 (7th February 2019) - Hards, Kiel; Rodriguez, Salome Molano; Cairns, Charlotte; Cook, Gregory M.
Abstract : There is a paucity of information on the unique components that pathogens use to form respiratory chains. It is not known why mycobacteria encode multiple succinate dehydrogenases (SDHs) to perform menaquinone‐linked succinate oxidation, a thermodynamically unfavorable reaction (Δ G ° = +21 kJ·mol −1 ). In other bacteria, specific di‐heme SDHs overcome this using the proton motive force. It is unknown if this holds true in mycobacteria. Here, succinate dehydrogenase 1 (Sdh1) from Mycobacterium smegmatis was purified and found to not contain heme cofactors. Proteoliposomes, containing Sdh1, are active with coenzyme Q2 ( K m  ~ 12 μm ), are competitively inhibited by menaquinone ( K i  ~ 25 μm ) and do not generate or consume electrochemical gradients. Sdh1 may use higher potential quinones in vivo and forms a novel SDH class, which we term 'Type F'. Abstract :